Substraty do procesu ko-fermentacji = Substrates for co-fermentation process - Sadecka, Zofia; Myszograj, Sylwia; Suchowska-Kisielewicz, Monika; Sieciechowicz, Aleksandra (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The integrated process of sludge treatment and waste can be realized in cofermentation processes. Such solutions provide not only better utilization of the available capacity of the existing bioreactors, but also, due to the appropriate choice of substrates, increase the production of biogas from a parallel solution to waste management in municipalities.
Keywords: ko-fermentacja metanowa; osady ściekowe; odpady; biogaz; methane co-fermentation; sewage sludge; wastes; biogas